(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: This study aims to identify the culprits and assess the risk of infertility in male patients. The characteristics of sperm, sperm DNA and chromosomes of groups of infertile patients, patients whose wives have a history of 2-3 consecutive miscarriages are compared to those with normal fertility. Methods: Analyze influencing factors, determine the possibility of sperm DNA breakage and the impact of abnormal chromosomes on fertility in men. Analyzing relevant factors, determining the possibility of sperm DNA fragmentation and the effect of abnormal chromosomes on fertility in men. Results: Semen volume, total sperm count, survival rate, pH, lysis time in infertile patients are lower, semen has high viscosity, low viscosity, acidic pH and normal sperm shape low, sperm mobility and movement speed were 2 - 3.3 times slower but the number of white blood cells and red blood cells was higher than other groups. Infertility appears at the age of 35-40, accounting for the highest rate of 36% (p<0.05), of which 100% of infertile patients have broken sperm DNA (p<0.05), 35% of patients whose wives had a history of 2-3 miscarriages had chromosomes of abnormal size and number, and did not appear in control group.